RdDM pathway components differentially modulate Tobamovirus symptom development - Leone, Melisa; Zavallo, Diego; Venturuzzi, Andrea Laura; Asurmendi, Sebastian (Springer, 2021)
Small RNAs (sRNAs) are important molecules for gene regulation in plants and play an essential role in plant-pathogen interactions. Researchers have evaluated the relationship between viral infections as well as the endogenous accumulation of sRNAs and the transcriptional changes associated with the production of symptoms, but little is known about a possible direct role of epigenetics, mediated by 24-nt sRNAs, in the induction of these symptoms. Using different RNA directed DNA methylation (RdDM) pathway mutants and a triple demethylase mutant; here we demonstrate that the disruption of RdDM pathway during viral infection produce alterations in the plant transcriptome and in consequence changes in plant symptoms. This study represents the initial step in exposing that DNA methylation directed by endogenous sRNAs has an important role, uncoupled to defense, in the production of symptoms associated with plant-virus interactions.